Computational analysis of US Congressional speeches reveals a shift from evidence to intuition - Segun Toafeek Aroyehun; Almog Simchon; Fabio Carrella; Jana Lasser; Stephan Lewandowsky; David Garcia (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Pursuit of honest and truthful decision-making is crucial for governance and accountability in democracies. However, people sometimes take different perspectives of what it means to be honest and how to pursue truthfulness. Here we explore a continuum of perspectives from evidence-based reasoning, rooted in ascertainable facts and data, at one end, to intuitive decisions that are driven by feelings and subjective interpretations, at the other. We analyze the linguistic traces of those contrasting perspectives in Congressional speeches from 1879 to 2022. We find that evidence-based language has continued to decline since the mid-1970s, together with a decline in legislative productivity. The decline was accompanied by increasing partisan polarization in Congress and rising income inequality in society. Results highlight the importance of evidence-based language in political decision-making.
urn:nbn:de:bsz:352-2-1vbw439suxx047
Keywords: 320